UNTANGLING THE DIGITAL EXHAUSTION (De Legibus - Revista de Direito da Universidade Lusófona Lisboa, 2021)
Through this essay, we will focus on the defensibility of a digital exhaustion principle in both legal and practical dimensions regarding the workability and acceptance under the new digital paradigm. The principle of exhaustion is expressively recognized at both the international and European level as a limit to the right of the original owner’s right of distribution. Attending to the meaning of frontiers in the digital ecosystem, hence the underlying idea behind the principle of exhaustion, is to facilitate the functioning of the internal market by eliminating the barriers to the free movement of goods within the European Union. To this end, we will analyse the applicability of the principle of exhaustion to the online dissemination of digital copyrightable content in the Digital Single Market attending to the existing statutory framework within  the EU along with the recent case law. While bearing in mind the existing challenges in the field of copyright law with the massive digitalization, the unprecedented number of copies available online facilitating piracy and dissemination at an almost near-zero cost. We will undertake a solution based on the synergy of means for policy in light of the 21st-century challenges and technologies available. Therefore, we propose a model that combines both legal and technological tools.